The Accuracy of Serum Biomarkers in the Diagnosis of Steatosis, Fibrosis, and Inflammation in Patients with Nonalcoholic Fatty Liver Disease in Comparison to a Liver Biopsy - Ivana Mikolasevic; Viktor Domislovic; Irena Krznaric-Zrnic; Zeljko Krznaric; Lucija Virovic-Jukic; Sanja Stojsavljevic; Ivica Grgurevic; Sandra Milic; Ivan Vukoja; Petra Puz; Merica Aralica; Goran Hauser (Medicina, 2022)
Background and Objective: This study was conducted to evaluate the diagnostic performance of various biomarkers for steatosis, fibrosis, and inflammation in comparison to a liver biopsy (LB) in patients with nonalcoholic fatty liver disease (NAFLD). Materials and Methods: This was a cross-sectional study that included 135 patients with biopsy-proven NAFLD. Fatty liver index (FLI), hepatic steatosis index (HSI), cell death markers (CK-18 M30 and CK-18 M65), FIB-4 index, NAFLD fibrosis score (NFS), BARD, and AST to platelet ratio index (APRI) were calculated and analysed. Results: FLI, HSI scores, and the cell death biomarkers showed poor diagnostic accuracy for steatosis detection and quantification, with an area under the curve (AUC) of <0.70. The cell death biomarkers likewise did not perform well for the detection of nonalcoholic steatohepatitis (NASH) (AUC < 0.7). As for the fibrosis staging, only APRI and the cell death biomarkers had moderate accuracy (AUC > 0.7) for advanced fibrosis, whereas FIB-4, BARD, and NFS scores demonstrated poor performance (AUC < 0.70). However, a combination of FIB-4 and NFS with the cell death biomarkers had moderate accuracy for advanced (≥F3) fibrosis detection, with an AUC of >0.70. Conclusions: In this first study on Croatian patients with NAFLD, serum biomarkers demonstrated poor diagnostic performance for the noninvasive diagnosis of liver steatosis and NASH. APRI and the cell death biomarkers had only moderate accuracy for diagnosing advanced fibrosis, as did the combination of FIB-4 and NFS with the cell death biomarkers. Further studies regarding serum biomarkers for all NAFLD stages are needed.